Psikoanalisis Lacan dalam Novel Harapan di Atas Sajadah Karya Mawar Malka - Annisa, Suci Dwi; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This research is motivated by literary works, which are a part of art that provides insights into human life. This study falls within the scope of psychoanalytic analysis, closely related to the personality of the characters in the novel. The aim of this research is to understand, analyze, and interpret the development of the characters' personalities in the novel "Harapan di Atas Sajadah" by Mawar Malka. The research employs a qualitative approach with a descriptive method. The hermeneutic technique is used for data collection, and the data analysis involves grouping, analyzing, interpreting, and drawing conclusions. The theoretical framework for this study is Mana Sikana's theory (2005). The primary data source is Mawar Malka's novel "Harapan di Atas Sajadah," consisting of 542 pages. The research findings include a total of 44 data points. The symbolic stage of character personality development comprises 29 data points, involving characters such as Pras, Adara, Devika, Andi, Nenek Karsimah, Haniyah, Haryu, and Rivan. The real stage of character personality development includes 15 data points, focusing on characters like Pras, Adara, and Haryu.